Changes crushing resistance (CR) of granulated aggregate obtained from fluidized bed fly ash (FBFA) processed in a CO2 atmosphere and seasoned in an of high humidity air - Bzowski, Zbigniew; Łączny, Jacek; Proksa, Jadwiga (Instal, 2023)
The aim of the research presented in the article was to investigate how the high-humidity air environment changes the crushing resistance (CR) of granulated carbonated fluidized bed fly ash (CGFBFA). It was assumed that CR influences the way it is used in geoengineering as a substitute for natural aggregates. The results of testing the granulate obtained in the three-phase carbonation reaction with carbon dioxide and granulation process in a multifunctional rotary granulator (MRG) are presented. The obtained product was exposed for a period of time three years in the conditions of the atmosphere of the mine gallery of the experimental mine. The air humidity ranged from 76% to 98% and the temperature ranged from approx. 6°C to approx. 14°C. The crushing resistance tests (CRT) of the samples were carried out using a SCHIMADZU AGX-300kN VINSTON hydraulic press (USA). Mineralogical studies were performed using the powder diffractometric method (DSH), using Bragg-Brentano geometry. The Bruker D8 Discover diffractometer, CuKa radiation, Ni filter and LYNXEYE_XE detector were used. Has been demonstrated, that the 3-year exposure of in the mine air atmosphere had a positive effect on the increase CR of CGFBFA, causing its increase from 5 MPa to 7.4 MPa, i.e. by approx. 32.4%. The increase of CR was interpreted as the result of the formation of relatively large amounts of gypsum in the composition in CGFBFA after the exposed period. Mineralogical research also leads to the preliminary conclusion that calcite and ettringite also play a role in this process. It was hypothesized that calcite is a binding factor at the stage of the carbonation process. We assumed that later, this too phase participating in the crystallization process of ettringite by replacing some of the sulfate ions (SO32-) with CO32– ions. As a result of this process, the conditions of thermodynamic equilibrium in ettringite may change, which favours the crystallization of gypsum. This issue will be the subject of further research. Research carried out and analyses showed that granulation of LPF in an atmosphere of carbon dioxide may be a prospective method of their management in combination with CO2 utilization. This idea is consistent with the EU strategy regarding the circular economy (CE) and carbon dioxide sequestration and utilisation(CCS/CCSU).